La obra poética de Damián Cornejo: cuatro manuscritos más y uno menos - Antonio Carreira (Criticón, 2008)
The present paper deals with the poetic work of fray Damián Cornejo (1629-1707), part of which was assigned to his colleague Manuel de León Marchante (1631-1680). At the same time it enumerates the integri manuscripts that transmit Cornejo’s work, adding four unknown poems, and suppressing one wrongly attributed to him.